Analysis of Microplastics of Bilih Fish (Mystacoleucus padangensis) in Lake Singkarak, West Sumatra Using FT-IR Spectroscopy - Ad'hani, Calysta Deli; Zulkarnaini, Zulkarnaini; Silvia, Shinta; Yuranda, Fitri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: Microplastics have become a global concern due to their wide distribution and ecological effects. Understanding the interactions between microplastics and ecosystems is important for environmental risk assessment. This study analyzed the abundance and distribution of microplastics in Lake Singkarak. Substantial microplastic research is still lacking for freshwater biota, so a study was conducted to determine the level of microplastic pollution in bilih fish tissue. The fish's size, weight, and sampling point were studied about microplastic uptake through two channels, digestion and respiration. From the results, the types of polymers identified in this study were polyethylene, polyvinyl chloride, and polyethylene terephthalate. Overall, 7.14% - 23.53% (average = 11.48%) of microplastics were identified in the D tract of bilih fish from sixteen different sampling points. While 7.69% - 17.39% (average = 11.85%) of microplastics were identified in the respiration of bilih fish. The highest percentage of the abundance of microplastic forms in the digestions identified was fiber at 70.42% and 66.82% in the digestions. At the same time, The lowest percentage identified was fragmented, with an average abundance of 29.58% in digestion and 33.32% in respiration. In conclusion, this study reveals the presence and impact of microplastics in Lake Singkarak, West Sumatra, on the bilih fish (Mystacoleucus padangensis). By examining the fish's digestive and respiratory systems and using FT-IR Spectroscopy, the research highlights the ecological and economic implications of microplastic pollution. These findings emphasize the need for targeted conservation and management strategies.Abstrak: Mikroplastik telah menjadi perhatian global karena distribusinya yang luas dan efek ekologisnya. Pemahaman tentang interaksi antara mikroplastik dengan ekosistem dinilai penting untuk penilaian risiko lingkungannya. Penelitian ini menganalisis kelimpahan dan distribusi mikroplastik di Danau Singkarak. Penelitian mikroplastik secara substansial masih sedikit untuk biota air tawar maka dilakukan penelitian untuk menentukan tingkat polusi mikroplastik pada jaringan ikan bilih. Ukuran, berat, dan titik sampling ikan diteliti dalam kaitannya dengan jerapan mikroplastik melalui dua saluran, yaitu digestif (pencernaan) dan respirasi (pernapasan). Dari hasil penelitian, jenis polimer yang teridentifikasi dalam penelitian ini adalah jenis polietilen, polivinil klorida, dan polietilen tereftalat. Secara keseluruhan 7,14% - 23,53% (rata-rata = 11,48%) mikroplastik teridentifikasi pada digestif ikan bilih dari enam belas titik sampling yang berbeda. Sementara 7,69% - 17,39% (rata-rata = 11,85%) mikroplastik teridentifikasi pada respirasi ikan bilih. Persentase kelimpahan bentuk mikroplastik tertinggi pada digestif yang diidentifikasi adalah fiber sebesar 70,42% dan 66,82% pada digestif. Sementara persentase terendah yang diidentifikasi adalah fragment dengan rata-rata kelimpahan sebesar 29,58% di digestif dan 33,32% di respirasi. Sebagai kesimpulan, penelitian ini mengungkap keberadaan dan dampak mikroplastik di Danau Singkarak, Sumatera Barat, pada ikan bilih (Mystacoleucus padangensis). Dengan memeriksa sistem pencernaan dan pernapasan ikan serta menggunakan Spektroskopi FT-IR, studi ini menunjukkan implikasi ekologis dan ekonomi dari polusi mikroplastik. Temuan ini menekankan perlunya strategi konservasi dan pengelolaan yang terarah.